SOLAR ABSORBING COOLING SYSTEMS BASED ON MULTISTAGE HEAT-MASS-TRANSFER DEVICES - Doroshenko A.V.; Ludnitsky K.V. (Problems of the Regional Energetics)
The article presents the worked out schematics for the alternative refrigeration systems and of air-conditioning systems, based on the use of absorbing cycle and of the sunny energy for the regeneration (renewals) of absorbent solution. We use here the cascade principle of construction of all heat-mass-transfer apparatus with variation of both the temperature level and the growth of absorbent concentration on the cascade stages. The heat-mass-transfer equipment as a part of the drying and cooling units is standardized and is executed by means of multistage monoblock compositions from poly-meric materials. The preliminary analysis of possibilities of the sunny systems in application to the tasks of cooling of environment and air-conditioning systems is carried out.